Bi-National Learning and the Internet: Grassroots Experiments in Global Education - Egnatoff, William J. (International Review of Research in Open and Distributed Learning, 2010)
Students at a French immersion high school in Ottawa and a school in Brazil exchange recipes, using a combination of French, English and Portuguese. The Brazilians discover they like poutine! Children in a rural Sierra Leonean village devastated during the civil war and a school in Mississauga collaborate to produce an online art gallery of pictures about what peace means to them. What do these examples and hundreds of thousands like them mean to the participants? What are the benefits and challenges of collaborating across countries and cultures in the design, implementation, and assessment of learning activities? Such activities by their collaborative nature support global education, whether it emphasizes peace, social justice, citizenship, ecology, or any topic or issue of shared interest. Bill Egnatoff will present a conceptual framework for bi-national collaboration of this sort. He will illustrate the framework from relevant literature, through his experience in teaching a course called Global Education Through International Collaboration, and through his peace education design research with colleagues in Canada and Sierra Leone. That work includes experimentation with, and evaluation of, a variety of tools and systems to support collaboration among twinned school communities, pre-service and in-service teachers, teacher educators, and researchers.